Decree-Law of the president of the Arab Republic of Egypt No. 198 of the Year 2014 Issuing the mineral Resources Law = قرار رئيس جمهورية مصر العربية بالقانون رقم 198 لسنة 2014 بإصدار قانون الثروة المعدنية / Egypt. Presidency - Egypt. Presidency (2025)
Decree law of the president of the Arab Republic of Egypt No. 198 of the year 2014 issuing the mineral resources law قرار رئيس جمهورية مصر العربية بالقاون رقم 198 لسنة 2014 بإصدار قانون الثروة المعدنية